Social Relations in Adolescents Based on Religion in Junior High School - Ditya Puspitasari; Sunarto Sunarto; Nur Afifah K.M. (Indonesian Journal of Humanities and Social Sciences, 2023)
This study aims to describe social relations based on religion in public schools at the junior high school. This study used qualitative methods with observational and interview data collection techniques. Data analysis techniques in this study use steps: Data reduction, displaying data, and drawing conclusions. The results showed that the majority of teenagers in junior high school did not choose friends based on religious considerations. They choose friends based on habits and ethics. However, there is a small percentage of children who are more comfortable making friends with co-religionists for several reasons. The form of tolerance between adolescents consists of five things. First, it allows other religions to worship according to their religion. Second, do not participate in celebrations or other religious rituals. Third, congratulate and support the practice of other religions. Fourth, invite friends of different religions to associate and interact, not discriminate, not oppress, and not harass other religions and not discriminate. Fifth, the school gives equal rights in all programs of intracurricular and extracurricular activities